FOSTERING SUSTAINABILITY AWARENESS AMONG SANATA DHARMA UNIVERSITY STUDENTS: THE ROLE OF PARTICIPATION, UNIVERSITY IMAGE, AND INSTITUTIONAL SUPPORT (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
This study examines the interplay between student participation, university image, and institutional support as influential elements in promoting pro-environmental behaviour among students at Sanata Dharma University, in light of the increasing importance placed on sustainable practices. Utilizing a sample size of 210 students from diverse academic areas, this research applies a multiple regression analysis to elucidate the complex interconnections within this particular setting. The research findings shed light on a complex and intricate portrayal. The study demonstrates that there is a noteworthy correlation between university support and active student participation, both of which have a substantial and positive impact on the development of environmental awareness among students. On the other hand, the university's perceived image, although crucial to its overall reputation, does not appear to have a substantial influence on students' environmental awareness. In light of these findings, it becomes apparent that strategic interventions should target the enhancement of student participation and the strengthening of institutional support in order to effectively foster sustainability consciousness within the student population at Sanata Dharma University. This revised analysis, enhances our comprehension of the underlying mechanisms, highlighting the pivotal significance of student engagement and institutional support in cultivating a sustainable mentality.
Keywords: Sustainability Awareness; Participation; University Image; Institutional Support